Amino acid composition in Malaysian rice varieties - Quah, S. C. (1981)
The amino acid content in the grain of eight Malaysian rice varieties which had been grown at three levels of nitrogen fertilization (0,60 and 120kgN/ha)were determined using the Beckman Amino-Acid Analyzer. It was found that the eight varieties examined varied significantly in their aminoacid content(g/lOOgsample)and in amino acid composition (g/lOOg protein) at each of the three nitrogen levels.The application of nitrogen fertilizers to the soil Significantly altered the amino acid content of the rice grain but not the amino acid composition.The mean value of the total amino acid content in the eight varieties showed an impressive increase of almost 13 percent,from 8.44g at zero nitrogen level to 9.55g at the highest nitrogen level. In terms of amino acid composition, the main amino acids in the rice grains are glutamic acid(16%),aspartic acid (9%), arginine(9%)and leucine(8%).The seven essential amino acids measured constituted almost one-third of the total amino acids estimated. Among the essential amino acids, leucine was the most abundant and methionine the least. The average content of lysine and threonine in the eight varieties were estimated at 4.2g/lOOg protein and,3.8g/l00g protein respectively.In terms of amino acid composition Malaysian rice varieties are just as nutritious as those from other countries.